See how They Grow : concepts in child development & parenting - Draper, Thomas, 1947-; Coleman, Marilyn; Goodell, Virginia (New York : Butterick Pub., 1980)
Discusses the physical and emotional development of a child from conception to adolescence and the involvement of the parents at each stage.
Includes bibliographical references ( p. 375-377) and index.
Keywords: Child development; Parenting; Child development; Parenting